A Circular RNA, Cholangiocarcinoma‐Associated Circular RNA 1, Contributes to Cholangiocarcinoma Progression, Induces Angiogenesis, and Disrupts Vascular Endothelial Barriers. Issue 4 (13th April 2021) - Xu, Yi; Leng, Kaiming; Yao, Yue; Kang, Pengcheng; Liao, Guanqun; Han, Yi; Shi, Guangjun; Ji, Daolin; Huang, Peng; Zheng, Wangyang; Li, Zhenglong; Li, Jinglin; et al.
Abstract : Background and Aims: Circular RNAs (circRNAs) and extracellular vesicles (EVs) are involved in various malignancies. We aimed to clarify the functions and mechanisms of dysregulated circRNAs in the cells and EVs of cholangiocarcinoma (CCA). Approach and Results: CircRNA microarray was used to identify circRNA expression profiles in CCA tissues and bile‐derived EVs (BEVs). CCA‐associated circRNA 1 (circ‐CCAC1) expression was measured by quantitative real‐time PCR. The clinical importance of circ‐CCAC1 was analyzed by receiver operating characteristic curves, Fisher's exact test, Kaplan–Meier plots, and Cox regression model. The functions of circ‐CCAC1 and exosomal circ‐CCAC1 were explored in CCA cells and human umbilical vein endothelial cells (HUVECs), respectively. Different animal models were used to verify the in vitro results. RNA sequencing, bioinformatics, RNA immunoprecipitation, RNA pulldown, chromatin immunoprecipitation followed by sequencing, and luciferase reporter assays were used to determine the regulatory networks of circ‐CCAC1 in CCA cells and HUVECs. Circ‐CCAC1 levels were increased in cancerous bile‐resident EVs and tissues. The diagnostic and prognostic values of circ‐CCAC1 were identified in patients with CCA. For CCA cells, circ‐CCAC1 increased cell progression by sponging miR‐514a‐5p to up‐regulate Yin Yang 1 (YY1). Meanwhile, YY1 directly bound to the promoter of calcium modulating ligand to activate its transcription. Moreover, circ‐CCAC1 from CCA‐derived EVs was transferred to endothelial monolayer cells, disrupting endothelial barrier integrity and inducing angiogenesis. Mechanistically, circ‐CCAC1 increased cell leakiness by sequestering enhancer of zeste homolog 2 in the cytoplasm, thus elevating SH3 domain‐containing GRB2‐like protein 2 expression to reduce the levels of intercellular junction proteins. In vivo studies further showed that increased circ‐CCAC1 levels in circulating EVs and cells accelerated both CCA tumorigenesis and metastasis. Conclusions: Circ‐CCAC1 plays a vital role in CCA tumorigenesis and metastasis and may be an important biomarker/therapeutic target for CCA.